Constructing with Compliance to Reliability and Maintenance - Kramberger, Janez (University of Maribor Press, 2017)
The textbook represents one of the few works in the Slovene language in the field of design of technical systems, while taking into account reliability and maintainability. The main purpose of the textbook is to present the possibilities and ways of improving the efficiency of technical systems in the design stage from the aspect of reliability and maintainability. The textbook is intended for students of mechanical engineering in the course Design for reliability and maintainability. Also it can be used for related subjects. The textbook can be an important source of information also for students of other technical faculties and for engineers who, in practice, deal with issues related to reliability, maintainability and safety of technical systems. This knowledge is now scattered across various books and references that are more difficult for users to access. The main purpose of this work is to bring this demanding topic in a simple way closer to users. For this reason, several short examples are included in each chapter of the textbook in order to clarify the subject under consideration and to present practical applications of the methods presented.